Perancangan Iklan Televisi (Tv Commercial ) Wisata Alam Air Terjun Sarasah Di Kota Padang - Rizky julian putra; Zubaidah A Zubaidah A; San ahdi (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Nature Tourism Sarasah Padang Waterfall as a nature tourism destination and a water vehicle in the city of Padang. This tourist spot is managed by local residents and young Koto Baru, led by Andreta Waldi as manager of Sarasah Waterfall Nature Tourism since 2013. This tourist address is located in Koto Baru Village, Gadut, Limau Manis Selatan Village, Pauh District, Kota Padang, West Sumatra Province. Sarasah waterfall nature tourism has considerable potential and opportunities to be developed, so that the target audience knows the existence of Padang Sarasah waterfall tourism. The basic problem is the lack of promotion of nature tourism in Sarasah Waterfall, the lack of information to the target audience. The purpose of television advertising can provide information, communicative with an attractive display of visualization to the target audience about the existence, nature tourism and water rides in the nature tourism of Padang Sarasah Waterfall.The design method uses a glass box, where the final result of a work is drawn from a rational process. Data collection used is a SWOT analysis (strength, weakness, opportunities and threats)The results of the design as the main media of television advertising and supporting media: Posters, Billboards, Banners, Stickers, Flayer, T-shirts and Hats.Keywords: Advertising, Television, Video, promotion, Nature Tourism